GAYA HIDUP KOMUNITAS ROKOK ELEKTRIK SEMARANG VAPER CORNER - Delima Rahayu Istiqomah; Kusyogo Cahyo; Ratih Indraswari (Jurnal Kesehatan Masyarakat (Undip), 2016)
Indonesia ranks third highest number of smokers in the world, thats why there is campaign to stop that. One of the alternatif ways to stop it by using electric cigarette, the teenagers do it only because of the trend. The purpose of this research to analyze lifestyle community elecetric cigarette Semarang Vaper Corner. The method used quantitative with cross sectional approach. The population are all members of the community of 98 people and the samples taken as many as 90 people using total sampling technique. Sources of data research using primary data and secondary data. Analyzed using univariate and bivariate statistical test Chi Square (significance level 0.05).  Most of the respondents were 17-25 years of age (late teens) (82.2%), most of the sex of the respondents were male (86.7%), the majority of respondents' education end of college graduates (41.1%) , respondents were mostly the work of entrepreneurs (26.7%), and the opinion of most of the above number Rp. 2,000,000 (92.2%). Knowledge is still lacking respondents (51.1%), positive attitude to using e-cigarettes (52.2%), respondents are motivated to use e-cigarettes (51.1%), the environment of respondents were smokers (80.0%), affordability of buying cigarettes electrical (60.0%), affordability of buying rechargeable electric cigarette (53.3%), lack of family support (52.2%), the support of the reference group (66.7%).  Chi Square test results found no relationship between sex , attitude , motivation , environment , affordability buy electric cigarette , and support reference group. As for age , the end of education , employment, income, knowledge, affordability buy rechargeable electric cigarette , and family support no association with the lifestyle of the community Semarang Vaper Corner . Suggestions for this study health agency immediately issued a decree regulating the electric cigarette so as to educate the public .